2015
DOI: 10.1371/journal.pone.0117291
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Juvenile Hormone Pathway in the Viviparous Cockroach, Diploptera punctata

Abstract: Juvenile hormones (JHs) are key regulators of insect development and reproduction. The JH biosynthetic pathway is known to involve 13 discrete enzymatic steps. In the present study, we have characterized the JH biosynthetic pathway in the cockroach Diploptera punctata. The effect of exogenous JH precursors on JH biosynthesis was also determined. Based on sequence similarity, orthologs for the genes directly involved in the pathway were cloned, and their spatial and temporal transcript profiles were determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 55 publications
2
35
0
Order By: Relevance
“…In B. germanica adult females, BgJHAMT mRNA was detected in CA, with only traces in ovaries. JHAMT has been also reported to be exclusively or very predominantly expressed in CA of all the insects where tissue expression has been tested (Shinoda & Itoyama, ; Niwa et al ., ; Sheng et al ., ; Marchal et al ., ; Nouzova et al ., ; Bomtorin et al ., ; Huang et al ., ; Lu et al ., ). With respect to the presence of JHAMT in ovaries, in A. aegypti it has been reported that ovaries can synthesize JH III from JHA III, which points to the occurrence of an operative JHAMT in this tissue (van Ekert et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…In B. germanica adult females, BgJHAMT mRNA was detected in CA, with only traces in ovaries. JHAMT has been also reported to be exclusively or very predominantly expressed in CA of all the insects where tissue expression has been tested (Shinoda & Itoyama, ; Niwa et al ., ; Sheng et al ., ; Marchal et al ., ; Nouzova et al ., ; Bomtorin et al ., ; Huang et al ., ; Lu et al ., ). With respect to the presence of JHAMT in ovaries, in A. aegypti it has been reported that ovaries can synthesize JH III from JHA III, which points to the occurrence of an operative JHAMT in this tissue (van Ekert et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The genes encoding the enzymes involved in both modules are highly enriched, or even exclusively expressed, in the CA cells9. In the lepidopteran Bombyx mori , the dipteran Aedes aegypti and the dictyopteran Diploptera punctata , the expression patterns of JH biosynthesis enzymes in the CA cells correlate well to the JH synthetic activity of the gland, suggesting that the fluctuations in JH synthesis are mainly controlled at the level of the expression of these enzymes910111213. Unfortunately, very few factors have been connected to the transcriptional control of JH synthesis to date.…”
mentioning
confidence: 99%
“…The enzymes of the MVAP are well conserved in eukaryotes. In insects, all the MVAP enzymes seem to be encoded by single-copy genes, and identification of predicted amino acid sequences in insect genomes was possible based on sequence homology [13,20,6,21,22,23]. The late steps of JH biosynthesis (JH-branch) were generally considered to be JH-specific [4], all the genes encoding these enzymes have now been identified in several insects using molecular approaches that included EST sequencing [19,13], mRNA differential display [18] or homology to orthologue enzymes [15,17,22].…”
Section: Genomics and Transcriptomics Studiesmentioning
confidence: 99%
“…Comprehensive studies on the expression of transcripts have been implemented in several holometabola and hemimetabola insects, including B. mori [20,24], Ae. aegypti [6,7], D. punctata [13,23] and Schistocerca gregaria [21]. The transcripts for most JH biosynthetic enzymes are highly enriched or exclusively expressed in the CA, and their expressions are often coordinated with JH titers [20,7,23].…”
Section: Genomics and Transcriptomics Studiesmentioning
confidence: 99%
See 1 more Smart Citation